A Simple, Semiclassical Mechanism for Activationless, Long RangeCharge Transport in Molecular Junctions. (1st April 2022) - Supur, Mustafa; McCreery, Richard L.
Abstract : Past reports on photocurrents in molecular junctions consisting of aromatic oligomers between electrical contacts reveal very low activation energies (<1 meV) and weak distance dependence for molecular layer thicknesses of 20–60 nm. Photocurrent transport mediated by sequential tunneling between adjacent subunit orbitals represents a "super highway" for charge transport with low activation barrier, field dependence and long range of at least 60 nm. In addition to photocurrents, such transport may be involved in dark currents for distances >10 nm, previously reported biological transport across μ m in bacterial nanowires, and >1 cm in cable bacteria.